Legal Framework Model for Sustainable Solid Waste Management in Indonesia: A Contemporary Environmental Fiqh Perspective - Maskun; Ratnawati; Wiranti; Asriyani; Jamal Aslan (MILRev: Metro Islamic Law Review, 2025)
Indonesia faces a severe solid waste crisis, with more than 60 million tons generated annually. Weak law enforcement and insufficient fiscal support—regional budget allocations averaging only 0.6–1% of APBD, far below the 3% benchmark—have further exacerbated the problem. This study aims to develop an integrative legal framework for sustainable waste management that harmonises national environmental law with contemporary Islamic environmental jurisprudence (fiqh al-biʾah). Methodologically, the research employs a systematic review and doctrinal–normative analysis. Data were collected and classified from national statutes, government regulations, regional bylaws, and peer-reviewed literature, as well as case studies from Surabaya, Banyumas, and DKI Jakarta. These materials were then analysed through the lens of uṣūl al-fiqh and qawāʿid fiqhiyyah, including the maxims lā ḍarar wa lā ḍirār, maṣlaḥah ʿāmmah, ḥifẓ al-biʾah, and the principle of istikhlāf. The findings reveal three critical gaps. First, underfunding hinders early-warning systems and sustainable infrastructure. Second, the absence of faith-based fiscal tools—such as Green Zakat and Eco-Waqf—limits financing capacity and raises questions of compatibility with APBN/APBD structures and formal zakat institutions. Third, regulatory disharmony between central and regional authorities undermines effective coordination. This study proposes a holistic model that mandates a minimum 3% APBD allocation, institutionalises Islamic green finance mechanisms, and scales up municipal innovations such as Surabaya’s community-based 3R programs. It also highlights the socio-political dynamics affecting the acceptance of religiously informed legal frameworks. The novelty of this research lies in embedding fiqh al-biʾah into positive law and policy instruments, offering a faith-grounded yet implementable roadmap for Indonesia’s sustainable waste governance.